A Live Experience of Four-Dimensional Structure. (February 2021) - Tyler, Christopher W.
Selective attention is well known for 2D patterns and perceptual alternations are well established for 3D structures projected into 2D, such as the Necker cube. Here, these concepts are extended to the spatial fourth dimension in the form of the mathematical structure of the 4D hypercube. In orthographic projection, its 2D outline figure has multiple and highly dynamic percepts of up to 28 different 3D interpretations, which correspond to local 3D views of the 4D hypercube. Thus, the spontaneous operations of perceptual processing can provide direct insight into conceptual structure in the fourth dimension.